The Relationship Between Asset Purchases, Monetary Aggregates, and Inflation Between 2007 and 2022 – an Example of the Federal Reserve - Csiki, Máté (Public Finance Quarterly, 2022)
The large asset purchase programs following the 2008 crisis led to a significant expansion of money aggregates, which led to an appreciation of the relationship between inflation and money supply. In this study, I analysed the changes in monetary aggregates caused by quantitative easing, the framework for the implementation of monetary policy with ample reserves and their impact on price levels using a vector autoregressive (VAR) model between 2007 and 2022 based on data for the United States. The study includes the pandemic after 2020, however, due to the limited length of time available and the uncertainty of the effects, the focus of the study is on pre-pandemic processes. Inflation fears caused by the significant expansion of the money supply during the period were not substantiated due to the increase of excess reserves, the changing monetary policy operational framework and negative output gap. According to the model monetary aggregate shocks are built into inflation expectations, changes in the money aggregates caused by asset purchases help the central bank to reach its medium-term inflation target.